PENGARUH PENGETAHUAN WAJIB PAJAK BADAN TERHADAP PENERIMAAN PAJAK PENGHASILAN (PPh) BADAN PADA KANTOR PELAYANAN PAJAK PRATAMA MANADO - Nangka, Yubilly M.G.R; Sabijono, Harijanto; Tangkuman, Steven (Universitas Sam Ratulangi, 2014)
Tax is a source of domestic financing that is in need to run the national development. This study was conducted aimed to determine the effect of knowledge of the corporate taxpayers for income tax at Manado Small Taxpayer Office. The method of data analysis used in this study is that a simple linear regression to determine the effect of independent variables on the dependent variable. Based on the research results, it can be concluded that the taxpayer knowledge had no significant effect on corporate income tax revenues.